Terrified : how anti-Muslim fringe organizations became mainstream - Bail, Christopher (Princeton University Press, 2014)
In July 2010, Terry Jones, the pastor of a small fundamentalist church in Florida, announced plans to burn two hundred Qur'ans on the anniversary of the September 11 attacks. Though he ended up canceling the stunt in the face of widespread public backlash, his threat sparked violent protests across the Muslim world that left at least twenty people dead. In Terrified, Christopher Bail demonstrates how the beliefs of fanatics like Jones are inspired by a rapidly expanding network of anti-Muslim organizations that exert profound influence on American understanding of Islam. Bail traces how the anti-Muslim narrative of the political fringe has captivated large segments of the American media, government, and general public, validating the views of extremists who argue that the United States is at war with Islam and marginalizing mainstream Muslim-Americans who are uniquely positioned to discredit such claims. Drawing on cultural sociology, social network theory, and social psychology, he shows how anti-Muslim organizations gained visibility in the public sphere, commandeered a sense of legitimacy, and redefined the contours of contemporary debate, shifting it ever outward toward the fringe. Bail illustrates his pioneering theoretical argument through a big-data analysis of more than one hundred organizations struggling to shape public discourse about Islam, tracing their impact on hundreds of thousands of newspaper articles, television transcripts, legislative debates, and social media messages produced since the September 11 attacks. The book also features in-depth interviews with the leaders of these organizations, providing a rare look at how anti-Muslim organizations entered the American mainstream.